Emotional Resistance In The Experience War Witness Trauma - Volkov, Kostyantyn (Psychological Counseling and Psychotherapy, 2025)
The article is devoted to the empirical substantiation of emotional resilience in the experience of war witness trauma on a sample of student youth. The purpose of the presented material is to empirically explicate the peculiarities of emotional resilience in the experience of war witness trauma. The basis is the methods of a bibliographic review of empirical sources on this issue, from 2015 to 2024, and empirical methods using diagnostic methods (Connor-Davidson Resilience Inventory Scale (CD-RISC), Symptom Questionnaire (SLR-90-R); Rogers-Diamond Socio-Psychological Adaptation Questionnaire, Plutchik-Kellerman-Conte Questionnaire; K. Izard; R. Janov-Bulman Basic Beliefs Scale; R. Tadeshi and L. Calhoun Posttraumatic Growth Questionnaire); statistical tools (data standardisation or z-transformation procedure, discriminant analysis, nonparametric Mann-Whitney test, factor analysis, multiple regression analysis). The results include a methodological presentation of theoretical assumptions about the conditionality of the experience of war witness trauma by real indicators of a person's mental state and indicators of emotional stability, which in the psychological alliance is a powerful personal resource for surviving the emotionally stressful situation of war. The developed empirical research programme and the set of methods used for mathematical processing of the research results made it possible to identify personal symptom complexes of emotional resistance for students with high and medium levels of stress resistance. The psychological profile of students with a high level of stress resistance is determined by the adaptive qualities of flexibility of thinking and behaviour, self-organisation and prosocial interaction with other people; and the psychological profile of students with an average level of stress resistance is characterised by purposefulness, a pronounced sense of justice, awareness of personal responsibility for life circumstances and the desire for dominance. The conclusions indicate that the results obtained can be successfully used by psychologists in the education system to monitor the psychological recovery and post-traumatic growth of students.